2020
DOI: 10.4314/jasem.v24i1.11
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of phosphorus uptake, growth and yield of sweet potato (<i>Ipomoea batatas</i>) with phosphorus fertilizers

Abstract: This research was carried out to determine the best phosphorus fertilizer for improvement of sweet potato phosphorus uptake, growth and yield. The phosphorus fertilizer sources used were organic (Pacesetter), single super phosphate and crystallizer while the sweet potato variety used was Shaba. The experiment was laid out in randomized complete block design (RCBD) with three replications. Sweet potato plants from plots treated with crystallizer fertilizer at the rate of 500kg/ha had the highest phosphorus upta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 1 publication
2
17
0
Order By: Relevance
“…Vine length differs due to the genetic makeup present in the genotypes as well as tolerance to the acidic soil environment. Results are in agreement with the findings of Kareem (2013), reported that medium sized vine length ranges from 140-180 cm gave the best yield of sweet potato. Similar results were found in literature stated that the vine length differ from 220.17-264.43 cm due to their genetic make-up of sweet potato.…”
Section: Length Of Vinesupporting
confidence: 92%
“…Vine length differs due to the genetic makeup present in the genotypes as well as tolerance to the acidic soil environment. Results are in agreement with the findings of Kareem (2013), reported that medium sized vine length ranges from 140-180 cm gave the best yield of sweet potato. Similar results were found in literature stated that the vine length differ from 220.17-264.43 cm due to their genetic make-up of sweet potato.…”
Section: Length Of Vinesupporting
confidence: 92%
“…photosynthesis, nitrogen fixan, nucleic acid biosynthesis, energy generation. Furthermore, it encouraged root growth and development ( Marschner, 2012 andKareem, 2013).…”
Section: Tuber Root Yield and Its Componentmentioning
confidence: 99%
“…The content of phosphorus (P) in many soils of the world is often low or occurs in fixed forms ( Yang et al, 2014 ; Roy et al, 2016 ). P is an essential nutrient for plant growth and development, as it affects P uptake and endogenous hormone metabolism ( Shen et al, 2012 ; Ding et al, 2021 ; Zhao et al, 2021 ), and its deficiency dramatically affects the productivity of crops, such as sweetpotatoes, potatoes, chillies, soybean, rice, and so on ( Sun et al, 2019 : Kareem et al, 2020 ; He et al, 2021 ; Khanal et al, 2021 ; Nyiraneza et al, 2021 ; Yang et al, 2022 ). Previous studies have focused on the role of P in its uptake, yield, shape of the storage root, starch content, and total sugar quality of sweetpotato ( El-Deen et al, 2011 ; Wang et al, 2017 ; Villordon et al, 2018 ; Munda et al, 2019 ; Kareem et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…P is an essential nutrient for plant growth and development, as it affects P uptake and endogenous hormone metabolism ( Shen et al, 2012 ; Ding et al, 2021 ; Zhao et al, 2021 ), and its deficiency dramatically affects the productivity of crops, such as sweetpotatoes, potatoes, chillies, soybean, rice, and so on ( Sun et al, 2019 : Kareem et al, 2020 ; He et al, 2021 ; Khanal et al, 2021 ; Nyiraneza et al, 2021 ; Yang et al, 2022 ). Previous studies have focused on the role of P in its uptake, yield, shape of the storage root, starch content, and total sugar quality of sweetpotato ( El-Deen et al, 2011 ; Wang et al, 2017 ; Villordon et al, 2018 ; Munda et al, 2019 ; Kareem et al, 2020 ). These mentioned studies reported that under the conditions of a certain cultivation density, the yield is determined both by the average number of storage roots per plant and storage root weight, and between these two factors, the average number of storage roots per plant makes a greater contribution to the yield ( Si et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%